Exploring the DEAR Time Program on Students Reading Habit: a Descriptive Study at SMP Kharisma Bangsa School of Global Education - Angelia, Yustitia; Abiedillah, Moh. Syarif Saifa; Salamah, Nurmala Aulia; Fahriany, Fahriany; Ieadaini, Fayza Nurul (Institut Agama Islam Negeri Palopo, 2024)
Establishing a reading habit in the current time is challenging due to the distraction of the fast-paced and digitally interconnected world. Despite the challenges, DEAR (Drop Everything and Read) has the potential to foster a love for reading and increase literacy among students. However, it is necessary to investigate its impact comprehensively to get more incredible data. This study aims to explore the DEAR time program on students' reading habits and attitudes toward in-depth interviews. The method of this study is a qualitative approach by descriptive and thematic analysis — involving open-ended and close-ended questions to obtain valuable data due to the experiences and perceptions of students participating in the DEAR Time program. The data were collected from 26 participating 8th graders at Kharisma Bangsa School. The finding showed that the DEAR time program substantially influences students' reading habits, including substantial improvements like vocabulary expansion and an understanding of a broader knowledge base in various subject areas. They assumed that The DEAR Time program effectively captivated their interest, encouraging a daily habit of independent reading with dedicated space and time to delve into books and fostering a sense of curiosity and a passion for reading.